Gut–Brain Axis: Potential Factors Involved in the Pathogenesis of Parkinson's Disease - Chao, Yin-Xia; Gulam, Muhammad Yaaseen; Chia, Nicholas Shyh Jenn; Feng, Lei; Rotzschke, Olaf; Tan, Eng-King (Frontiers in Neurology, 2020)
Increasing investigations in the past decades have identified the association of the gastrointestinal (GI) disorders to susceptibility and progression of Parkinson’s disease (PD). Gut-brain axis has been proposed to play important roles in the pathogenesis of PD. Though numerous studies have focused on the association, the direct evidence of the factors contributing to both conditions are yet to be confirmed. In this mini review, we have summarized the factors involved in both PD and GI disorders, focusing on the common genetics, altered gut microbiota, diet and potential involvement of mucosal immunity. Understanding the contribution of gut factors to PD will help to decipher the mechanisms leading to PD development. Despite the existing challenges, current research on gut-brain axies provides opportunities to identify early diagnosis markers and potential novel therapeutic strategies which targets to stop or slow down the progression of dopaminergic neuron demise and PD development.